Dynamic simulation of China's water-grain-meat system and evaluation of its support capability based on water footprint theory - Jiang, Qiuxiang; Liao, Haoyu; Ouyang, Xingtao; Fu, Qiang; He, Xiaolong; Wu, Yunxing; Wang, Zilong (International Journal of Agricultural and Biological Engineering, 2023)
The supply capacity of water resources, food and meat products is of great importance to the people's livelihood of a country. In recent years, although China has introduced many policies on water resources and grain production, the current situation of China's food self-sufficiency and imbalance between supply and demand of water resources has not been fundamentally changed. Food security and water security are facing a serious situation. This paper takes the water footprint as the connection point, and combines the water food meat system with mutual influence, mutual causation and dynamic feedback into a composite system. At the same time, the simulation model of the composite system is established by using system dynamics, and the dynamic simulation of water grain meat in China from 2000 to 2050 is carried out to explore the current situation and future development trend of China's water, grain and meat supply capacity. It was found that during the simulated period, the agricultural blue-green water footprint on the demand side would continue to dominate, followed by the gray water footprint. The blue water footprint on the supply side remained stable, whereas the green water footprint and the circulating water footprint showed an upward trend. According to the contemporary social and economic development and the model of water resources in China, there will be no meat shortage in the future, but issues have been found in the ability to guarantee water and food supply. The root of China’s food support capability problem is excessive grain consumption due to meat production, whereas the cause of the water support capability problem is the slow development of the water conservation. Food support capability issues can be solved by regulating the meat output of livestock farming and fishery operations, reducing excess production capacity, and stabilizing the meat supply and demand. To solve the water support capability issue, China should focus on accelerating the pace of agricultural water-conservation development, improving the sewage treatment system, building rainwater-collection projects, and promoting the research and development of water recycling technology. This study provides support for optimizing the structures of the meat and grain industries and the policy formulation of the efficient use of water resources in China.Keywords: system dynamics, water footprint, evaluation, water support capability, food support capability, meat support capabilityDOI: 10.25165/j.ijabe.20231605.7458Citation: Jiang Q X, Liao H Y, Ouyang X T, Fu Q, He X L, Wu Y X, et al. Dynamic simulation of China's water-grain-meat system and evaluation of its support capability based on water footprint theory. Int J Agric & Biol Eng, 2023; 16(5): 270-282.